Mental health and quality of life of university professors (Research, Society and Development, 2022)
The objective is to review the profile of mental health during the Covid-19 pandemic, of university professors. It is a review of the literature, of an integrative type, elaborated by means of scientific articles, indexed in databases, including not the VHL REGIONAL PORTAL, using the following Descriptors in Health Sciences (DeCS): “Teaching”, “Health Mental” , “Pandemic”. To perform a cross using the controls described with the boolean operator helper “AND”. The category “Health and mental health not working as a teacher” arose from the large number of problems that this group faces, both physical and psychological. Among the main physical problems that these are susceptible to develop, we can highlight the vocal and musculoskeletal disorders and the psychic ones, two of the main ones have been Bornout Syndrome, which is mainly caused by constant exposure to stressful factors, in addition to which we also highlight depression and anxiety The workplace is seen by many as a main cause for the development of stress, mainly with the changes and technological advances that we see occurring or that make these environments more competitive. It was concluded, as well, that the work had a direct influence on QV and on the health of two higher level teachers. Devaluation, excessive work loads, double shifts, inadequate infrastructure, changes in the education process, are some two factors that generate feelings of impotence, anguish, stress and professional exhaustion, favoring physical and mental ill health.